Detection of ESBL-Producing Escherichia coli in Dogs Transported Through Juanda International Airport Quarantine, East Java, Indonesia - Benny Perdana; Mustofa Helmi Effendi; Wiwiek Tyasningsih; Wiwik Misaco Yuniarti; Boedi Setiawan; Dadik Rahardjo (Universitas Airlangga, 2026)
Antibiotic resistance poses a serious threat to global health, affecting both human and animal health sectors. Antibiotic resistance can be found in both healthy and diseased animals and may also be detected in their owners. Close interaction between humans and their pets, particularly dogs, can facilitate the transmission of antibiotic-resistant bacteria. Extended-spectrum beta-lactamase (ESBL) is one of the mechanisms of antibiotic resistance. Escherichia coli is an ESBL-producing bacterium that inhabits the gastrointestinal tract of living organisms, including humans and dogs. Infections caused by E. coli may lead to diseases, such as urinary tract infections. Infections involving antibiotic-resistant E. coli result in more difficult and prolonged treatment. This study aimed to detect ESBL-producing E. coli in dogs transported through Juanda International Airport. Rectal swabs were collected as samples. Bacterial identification was performed using EMB agar, Gram staining, and biochemical tests. Confirmation of ESBL-producing E. coli was performed using the double-disk synergy test (DDST). The results showed that 75.22% (85/113) were positive for E. coli, with 2.6% (3/113) confirmed as ESBL-producing by DDST.